(untitled) (INNOVATIVE ECONOMY, 2025)
Hryshchyshen S.V. THE IMPACT OF MACROECONOMIC TURBULENCE ON THE INVESTMENT ACTIVITY OF TRANSNATIONAL CORPORATIONS Purpose. The aim of the article is a comprehensive analysis of the impact of macroeconomic turbulence on the investment activity of transnational corporations, taking into account current trends in the global economy and examples for 2020-2024. Methodology of research. The research methodology is based on a combination of systemic and comparative analysis, the use of statistical data from international financial organizations, a case method for studying examples of the activities of leading TNCs, as well as elements of trend analysis to identify patterns in changes in investment activity. Findings. The results of the study show that macroeconomic turbulence in the form of inflationary surges, currency fluctuations, increases in interest rates, energy shocks and geopolitical conflicts leads to an increase in the cost of capital, limited access to debt financing and a reorientation of TNC strategies to less risky investments. The example of transactions proves that high rates make such operations economically unattractive, and the cases of companies demonstrate a shift in focus towards domestic investments and regionalization of production. It was found that in conditions of turbulence, TNCs more actively use friend-shoring models, digitalization of supply chains and diversification of sales markets. The study also showed that regional differences in the impact of turbulence depend on the level of economic stability and political stability of host countries. Originality. A comprehensive assessment of the cumulative impact of key factors of macroeconomic turbulence on the investment behaviour of TNCs, with the integration of data for 2020-2024 and a comparison of global and regional trends, has been further developed. Practical value. The practical significance of the research results lies in the possibility of using the obtained conclusions to develop adaptive investment strategies of TNCs and improve mechanisms for state support of foreign investments in periods of instability. Key words: international business, investment activity, currency volatility, inflation, friend-shoring, global risks.